(untitled) (BIRDEM Medical Journal, 2013)
Hyperprolactinemia is frequently diagnosed endocrine problem in routine clinical practice. Once hyperprolactinemia is suspected, repeat test for s prolactin can be done with appropriate precondition for sampling like rest, single prick, adequate light etc. to exclude macroprolactinemia specially in asymptomatic or unrelated symptoms. Once diagnosed as Hyper prolactinemia, secondary causes should be ruled out by history, specially drugs. Pregnancy should be excluded by history and if indicated, by test. Mild elevation of s prolactin can be also due to Polycystic Ovary Syndrome (PCOS), hypothyroidisom, CKD, CLD etc. Of course Hook Effect should be kept in mind. Contrast MRI should be done to see if there is any prolactinoma or hyperplasia. Sometimes Growth Hormone (GH) secreting tumors may be associated. Rarely extra pituitary tumors or disconnection of hypothalamus-pituitary may be seen. In symptomatic patient (hypogonadism, infertility, menstrual disturbances, sexual weakness, unexplained low bone mass and sometimes galactorrhoea etc) and specially if s prolactin is more than 2-3 times of upper limit of reference range, MRI with contrast should be done. Medical therapy with dopamine agonist is the treatment of choice for symptomatic any level of s prolactin and with prolactinoma. Cabergoline may be tried as a first line of treatment because it is more effective and better tolerated than bromocryptine. Though cabergoline is coming up with safety issues, bromocriptine has the largest safety database in pregnancy till date. All patient should be tried with medical treatment, specially cabergoline irrespective of symptoms and size of the tumor. Transsphenoidal microsurgery remains second option when medical treatment is ineffective. Radiotherapy may be the last adjuvant in the management . Rarely malignant prolactinoma may be found and have poor response to medical treatment. Birdem Med J 2013; 3(2): 99-105 DOI: http://dx.doi.org/10.3329/birdem.v3i2.17214